IMPROVING RESULTS BY ANALYZING TACTICS IN THE 4 KM INDIVIDUAL PURSUIT - Xamrayev, Sardor Sobirjon o‘g‘li (Educational Research in Universal Sciences, 2023)
The individual pursuit race exists in the track disciplines of cycling, and in this research work, the main focus is on improving results by moving along the trajectories of turns and turns (zones) and proves its effectiveness.